2015
DOI: 10.1371/journal.pone.0128642
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Clinicopathology Significance of MicroRNA-200c Expression in Cancer: A Meta-Analysis

Abstract: MiR-200c has been shown to be related to cancer formation and progression. However, the prognostic and clinicopathologic significance of miR-200c expression in cancer remain inconclusive. We carried out this systematic review and meta-analysis to investigate the prognostic value of miR-200c expression in cancer. Pooled hazard ratios (HRs) of miR-200c for overall survival (OS) and progression-free survival (PFS) were calculated to measure the effective value of miR-200c expression on prognosis. The association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…We found an association of miR-200c with bone metastasis, PSA level > 10.0 ng/μL, and bilateral tumor. In agreement with Wu et al [ 68 ] and Bryant et al [ 69 ], we suggested that this miRNA is a potential prognostic marker for PCa.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found an association of miR-200c with bone metastasis, PSA level > 10.0 ng/μL, and bilateral tumor. In agreement with Wu et al [ 68 ] and Bryant et al [ 69 ], we suggested that this miRNA is a potential prognostic marker for PCa.…”
Section: Discussionsupporting
confidence: 93%
“…A positive correlation was observed between miR-200c and GS; the higher expression levels of miR-200c, the higher the GS. According to Wu et al [ 68 ] miR-200c is a good candidate marker for PCa detection. We found an association of miR-200c with bone metastasis, PSA level > 10.0 ng/μL, and bilateral tumor.…”
Section: Discussionmentioning
confidence: 99%
“… 15 The following items were extracted: 1) publication details, such as the first author’s name and the publication year; 2) the characteristics of the studied population, including ethnicity, type of disease, detected sample, design of the study, detection method, cutoff definition, and follow-up time; and 3) HR of miR-150 expression for OS and PFS along with the 95% CI and P -value. If HRs were not reported in the article, we used Engauge Digitizer Version 4.1 (free software downloaded from http://sourceforge.net ) 16 to read the Kaplan–Meier survival curves to obtain the HRs and their 95% CIs. If there were insufficient data, controversies, or any other uncertainties in an article that might be related to our meta-analysis, we asked the corresponding authors for additional information.…”
Section: Methodsmentioning
confidence: 99%
“…Bootstrap re-sampling procedures were applied to investigate the association between SIRT1 expression and TNM stage in order to get robust and reproducible results [ 23 ] ( Supplementary Excel File S1 ). One randomly generated results are summarized in Supplementary Excel File S2 .…”
Section: Resultsmentioning
confidence: 99%
“…Only the biomarkers that more than two studies reported could be included in our clinicopathologic analysis. Bootstrap re-sampling procedure was used to validate the association between SIRT1 expression and TNM stage as we described previously [ 23 ]. The re-sampling statistic program was displayed in Supplementary Excel File S1 .…”
Section: Methodsmentioning
confidence: 99%